The Effect of Hypothyroidism on the Body Weight of Adult Albino Wistar Rats - Nida Qasim Hayat ,Shahnila Nadir , Mah Jabeen Muneera (Journal of Rawalpindi Medical College, 2016)
Background: To study the alteration in the body weight of adult albino rats in hypothyroid state. Methods: In this experimental animal study, change in the body weight of adult albino wistar rats was measured after they were made hypothyroid. Twenty adult albino wistar rats with average weight of 130-150 gms were randomly assigned into two groups. Group A served as control and Group B served as experimental group. The rats in group A were kept as control and given normal food and water ad libitum whereas Group B were administered Methimazole 0.02% for 22 days in drinking water. Body weight was recorded at the beginning and on alternate days. Results: MMI treatment produced significant influence on the body weight of the animals. Significant difference was observed in the initial and the final body weight of the control and the experimental group of animals, p<0.01. Conclusion: Hypothyroidism caused increase in the body weight of the experimental albino rats but decreased as compared to previous experimental studies.